Influence of innovative activity on the structure of assets of the enterprise - Kovalchuk, N.O.; Humeniuk, M.M. (SI Universum, London, 2019)
The research assesses the impact of the intensity of the enterprise's innovation activity on the structure of the assets of the enterprise, justifies the importance of optimizing the structure of assets to ensure the effective operation of the enterprise. The main reasons for decrease of investment activity of enterprises of Ukraine are determined and described.
Keywords: innovative activity; assets; efficiency of management